Respostas
respondido por:
1
Produto da soma:
(x + y)² =
(x + y) * (x + y) =
x² + xy + xy + y² =
x² + 2xy + y²
Produto da soma pela diferença:
(x + y) * (x - y) =
x² - xy + xy - y² =
x² - y²
Produto da diferença:
(x - y)² =
(x - y) * (x - y) =
x² - xy - xy + y² =
x² - 2xy + y²
(x + y)² =
(x + y) * (x + y) =
x² + xy + xy + y² =
x² + 2xy + y²
Produto da soma pela diferença:
(x + y) * (x - y) =
x² - xy + xy - y² =
x² - y²
Produto da diferença:
(x - y)² =
(x - y) * (x - y) =
x² - xy - xy + y² =
x² - 2xy + y²
aluno71:
muito obrigado !
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás